A Study of Sedentary Behaviour in the Older Finnish Twin Cohort: A Cross Sectional Analysis. (15th April 2014) - Piirtola, Maarit; Kaprio, Jaakko; Ropponen, Annina
Abstract : The aim of the study was to investigate the effects of age, sex, and body mass index (BMI) on total sitting time among the Finnish twin cohort. Also, heritability and environmental factors were analysed. The final sample included 6713 twin individuals 53–67 years of age (46% men). Among them there were 1940 complete twin pairs (732 monozygotic [MZ] and 1208 dizygotic [DZ] twin pairs). Sedentary behaviour was queried with a self-reported questionnaire with multiple-choice questions about sitting time at different domains. The mean total sitting time per day was 6 hours 41 minutes (standard deviation: 2 hours 41 minutes). The total sitting time was less in women than in men (P = 0.002 ). Older age was associated with less total sitting time (P < 0.001 ). Those with higher body mass index had higher total sitting time in age and sex adjusted analysis (P < 0.001 ). MZ pairs were more similar for sitting time than DZ pairs, with initial estimates of heritability for the total sitting time of 35%.The influence of shared environmental factors was negligible (1%), while most (64%) of the variation could be ascribed to unique environmental factors, the latter including measurement error.